Urgensi Manajeman Pendidikan Islam dalam Pengembangan Lembaga Pendidikan Islam - Marzuki Marzuki (Departement of Mathematics Education, 2024)
Education management is a system for regulating the implementation of education so that it meets the desired targets. Education management will regulate various policies in an education system. This research aims to explain the urgency in developing Islamic educational institutions. This type of research is qualitative with a Library Research approach. Research data consists of data about the urgency of educational management, Islamic educational institutions from primary sources in the form of relevant books and journals. Based on the research results obtained, Based on the overall description, the urgency of Islamic education management in the development of Islamic educational institutions is very important and cannot be ignored. In an ever-changing and complex context, Islamic education management plays a key role in ensuring that educational institutions remain relevant, of high quality and in accordance with Islamic values. With effective educational management, Islamic educational institutions can: 1) Maintain the identity and mission of the institution in teaching and applying Islamic values ​​consistently. 2) Explaining relevant synchronization and integrating Islamic values ​​into the learning process. 3) Improving the quality of teaching and learning with methods that are in accordance with Islamic principles. 4) Manage resources efficiently to support the operations of educational institutions. 5) Developing student character and ethics based on Islamic values. 6) Overcoming contemporary challenges with an Islamic perspective that is in line. 7) Make a significant contribution to the development of society as a whole. Thus, Islamic education management is not only important for the continuity and progress of Islamic educational institutions themselves, but also for the holistic growth of students and the development of society at large. Therefore, investment in Islamic education management is a crucial strategic step in ensuring that Islamic education institutions can function optimally and provide a sustainable positive impact on individuals and society.